Unexpected dilatation of the common bile duct after methyl tertiary butyl ether (MTBE) in rabbits. Possible implications to findings in man. Issue 2 (February 1989) - Tritapepe, R; Pozzi, C; Caspani, P; Di Padova, C
Abstract : Methyl tertiary butyl ether (MTBE) rapidly dissolves cholesterol gall stones in vitro and in vivo. To further characterise tolerability and safety of this aliphatic ether, either MTBE (1 ml/kg body wt daily for two days) or an equal amount of saline was infused into the common bile duct (CBD) of eight cholecystectomised rabbits. Transient vomiting, dyspnoea and somnolence developed during MTBE instillation. Post-treatment values of serum transaminases and alkaline phosphatase were significantly higher in MTBE than in saline treated animals. Cholangiography one week after the last intraductal infusion showed a five-fold increase of CBD size in MTBE v control rabbits. At autopsy histological signs of chemical cholangitis and mild duodenitis were noted in MTBE treated animals. Prompted by these findings, we performed a cholangiography in two patients who had received intraductal MTBE (about 0.2 ml/kg body wt daily for one or two days) one year before: an abnormal dilatation of the CBD was present, which might represent a specific, hitherto undescribed permanent sequela of MTBE administration.